Chronotype and the Big-Five personality traits as predictors of chronic fatigue among patients with sarcoidosis. A cross-sectional study - Mokros, Łukasz; Miłkowska-Dymanowska, Joanna; Gwadera, Łukasz; Pietras, Tadeusz; Piotrowski, Wojciech (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background. Sarcoidosis may seriously hamper patients’ quality of life despite fairly good prognosis. Objectives. To assess the relationship between the Big Five personality traits, chronotype and severity of fatigue symptoms, in the context of selected clinical variables and general mental health among patients with sarcoidosis. Methods. The study group comprised 60 patients with a confirmed diagnosis of sarcoidosis. They were asked to share relevant clinical data and complete a set of questionnaires: Fatigue Asessment Scale (FAS), General Health Questionnaire (GHQ-28), the NEO Five Factor Inventory and Composite Scale of Morningness. Results. In linear regression analysis, FAS score was predicted by female sex, active sarcoidosis status, Morning Affect and Conscientiousness. In principal component analysis, FAS score and all GHQ-28 subscale scores (somatic symptoms, anxiety/insomnia, social dysfunction and depressive symptoms) formed a single component explaining 60% of variance. The factor loading for each variable exceeded 0.6. Conclusions. The psychological burden appeared to rise with the severity of the fatigue, regardless the inactive/active phase of sarcoidosis. The severity of fatigue may be linked to patient’s poor morning affect. The profile of psychological burden presented by the patients may be associated with their personality and clinical presentation of sarcoidosis.